ANALISIS PERAN KEPALA SEKOLAH SEBAGAI COACH DALAM PENERAPAN COACHING MODEL TIRTA UNTUK MENINGKATKAN PROFESIONALITAS GURU DI KECAMATAN PURWODADI KABUPATEN GROBOGAN - Wiyati, Indar; Darmuki, Agus; W., Sri Surachmi (Universitas Muria Kudus, 2025)
This study aims to analyze the role of the principal as a coach in the implementation of the TIRTA coaching model to improve teacher professionalism in Purwodadi District, Grobogan Regency. This study uses qualitative research with a case study approach. The study was conducted in Purwodadi District, Grobogan Regency with informants of principals, supervisors, teachers, and administrative staff. Data were collected through interviews, observations, and document analysis. Data validation techniques used triangulation of time, sources, and methods. The results of the study indicate that principals in Purwodadi District have played an active role as coaches in implementing the TIRTA coaching model. The implementation of this model has a positive impact on improving teacher professionalism, including improving pedagogical competence, motivation, and teacher performance. However, there are several challenges in the implementation of the TIRTA coaching model, such as limited time and resources. This study suggests the need for increased support and training for principals as coaches to optimize the implementation of the TIRTA coaching model in improving teacher professionalism.